Women with COPD from biomass smoke have reduced serum levels of biomarkers of angiogenesis and cancer, with EGFR predominating, compared to women with COPD from smoking. (31st March 2021) - Montaño, Martha; Pérez-Bautista, Oliver; Velasco-Torres, Yadira; González-Ávila, Georgina; Ramos, Carlos
The main causes of COPD are smoking (COPD-TS) and exposure to biomass smoke (COPD-BS), considered as different phenotypes. The association of COPD-TS with lung cancer (LC) is well established, but not in COPD-BS. Thus, we studied the serum concentration of cytokines that participate in inflammation, angiogenesis, and tumor progression, used frequently as LC biomarkers, in women with COPD-BS compared with COPD-TS (n = 70). Clinical and physiological characteristics and the serum concentration (multiplex immunoassay) of 16 cytokines were evaluated. The analysis revealed that women with COPD-BS were shorter and older, and had lower concentrations of 12 serum cytokines: 6 proinflammatory and angiogenic IL-6Rα, PECAM-1, leptin, osteopontin, prolactin, and follistatin; and 6 that participate in angiogenesis and in tumor progression FGF-2, HGF, sVEGFR-2, sHER2/neu, sTIE-2, G-CSF, and SCF. Notably, there was a significant increase in sEGFR in women with COPD-BS compared to women with COPD-TS. PDGF-AA/BB and sTIE-2 did not change. These findings suggest that women with COPD-BS have markedly decreased proinflammatory, angiogenic, and tumor progression potential, compared to women with COPD-TS, with sEGFR as the predominant mediator, which might reflect a differential pattern of inflammation in women exposed to BS, favoring the development of chronic bronchitis.